The Confluence of Stereotactic Ablative Radiotherapy and Tumor Immunology. (15th November 2011) - Finkelstein, Steven Eric; Timmerman, Robert; McBride, William H.; Schaue, Dörthe; Hoffe, Sarah E.; Mantz, Constantine A.; Wilson, George D.
Abstract : Stereotactic radiation approaches are gaining more popularity for the treatment of intracranial as well as extracranial tumors in organs such as the liver and lung. Technology, rather than biology, is driving the rapid adoption of stereotactic body radiation therapy (SBRT), also known as stereotactic ablative radiotherapy (SABR), in the clinic due to advances in precise positioning and targeting. Dramatic improvements in tumor control have been demonstrated; however, our knowledge of normal tissue biology response mechanisms to large fraction sizes is lacking. Herein, we will discuss how SABR can induce cellular expression of MHC I, adhesion molecules, costimulatory molecules, heat shock proteins, inflammatory mediators, immunomodulatory cytokines, and death receptors to enhance antitumor immune responses.